Wage negotiations and strategic responses to transparency - Peter Werner (ZBW - Leibniz-Informationszentrum Wirtschaft, 2019)
This paper investigates how negotiations between employers and employees respond to exogenous and endogenous wage transparency. In a treatment with exogenous wage transparency, employers' offers increase significantly compared to the case when offers are private information. Moreover, the share of equal wage offers becomes larger. Employers and employees rarely induce transparency themselves. In a treatment where employees could enforce transparency, average wage offers are significantly lower than in the other treatments. Thus, employees forego potential wage increases by staying ignorant about co-workers' offers. Taken together, these findings have important implications for recent policies aimed at increasing wage transparency.
Keywords: D91; J31; M52; 330; Wage transparency; wage negotiations; real-effort; gift exchange; experiment